The impact of international environmental agreements: The case of the Montreal Protocol - Timothy Swanson; Robin Mason (Fondazione Eni Enrico Mattei (FEEM), 2002)
There has been a recent economic literature arguing that international environmental agreements (IEAs) can have no real effect, on account of their voluntary and self-enforcing nature. This literature concludes that the terms of IEAs are the codification of the noncooperative equilibrium, and recent empirical work has supported this conclusion in the context of the Montreal Protocol. This paper reaches the opposite conclusion, by means of the comparison of the CFC emissions implicit within the cooperative and noncooperative management paths. The cooperative path is implicit within the terms of the Montreal Protocol. The noncooperative path is implicit in countries' behaviour during the period of unilateral management of CFC emissions. This study estimates the relationship between countries' propensities to produce CFCs and income per capita over the period 1976-1988 (prior to the entry into force of the Montreal Protocol). It then extrapolates this path of unilateral management beyond 1988, and compares it to the obligations adopted under the cooperative regime. This comparison of the projected noncooperative path with the obligations adopted under the Montreal Protocol allows a qualitative test of theories on the economic foundations of self-enforcing IEAs. We find that, in the absence of the Protocol, CFC production (and hence emissions) would have increased by a factor of three over the next fifty years. This study also supplements existing environmental Kuznets curve analyses by providing estimates for the unilateral management for a global externality. In this manner we are able to assess the distributive impacts of the Protocol, in addition to its effectiveness. Using dynamic estimation methods on a panel of around 30 countries over 13 years, the turning point in the relationship between CFC production and income is found to lie around (1986) US16,000. This implies that developing countries bear the greatest costs in the implementation of the Montreal Protocol.
Keywords: D62; O13; Q20; 330; IEA; CFC; Montreal Protocol; Kuznets curves; Umweltabkommen; FCKW; Umweltpolitik; Wirtschaftswachstum; Welt